An extensive review on phenolic compounds and their potential estrogenic properties on skin physiology - Rispo, Francesca; De Negri Atanasio, Giulia; Demori, Ilaria; Costa, Giosuè; Marchese, Emanuela; Perera-del-Rosario, Simón; Serrano-Candelas, Eva; Palomino-Schätzlein, Martina; Perata, Elisabetta; Robino, Federica; Ferrari, Pier Francesco; Ferrando, Sara; et al. (Frontiers in Cell and Developmental Biology, 2024)
Polyphenolic compounds constitute a diverse group of natural components commonly occurring in various plant species, known for their potential to exert both beneficial and detrimental effects. Additionally, these polyphenols have also been implicated as endocrine-disrupting (ED) chemicals, raising concerns about their widespread use in the cosmetics industry. In this comprehensive review, we focus on the body of literature pertaining to the estrogenic properties of ED chemicals, with a particular emphasis on the interaction of isoflavones with estrogen receptors. Within this review, we aim to elucidate the multifaceted roles and effects of polyphenols on the skin, exploring their potential benefits as well as their capacity to act as ED agents. By delving into this intricate subject matter, we intend to provoke thoughtful consideration, effectively opening a Pandora's box of questions for the reader to ponder. Ultimately, we invite the reader to contemplate whether polyphenols should be regarded as friends or foes in the realm of skincare and endocrine disruption.